2019
DOI: 10.1111/ajr.12545
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of melanoma in rural southern Queensland

Abstract: Objective:The objective of this study is to define the epidemiology of melanoma in rural communities in southern Queensland. Design: The design used was a 6-year clinical record audit of melanoma cases identified by billing records and electronic clinical records, confirmed and typed with histology. Setting and Participants: This study was based on seven agricultural communities on the Darling Downs with patients presenting to local primary care clinics. Main outcome measures: Outcomes measured were confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…8,10,12,16,40 In adults with darker skin, the melanomas were more common in lower limbs, hips, and trunk, but in adults with lighter skin, melanomas were more predominant in sun-exposed sites, especially the head and neck, but could also be found in the trunk and upper limbs. [41][42][43][44] Possible differences in sun exposure behaviors might result in different sites of melanoma occurrence. 5 In our study, we have found that the majority of our melanomas have developed in the trunk with the highest mortality at 38%.…”
Section: Anatomical Distributionmentioning
confidence: 99%
“…8,10,12,16,40 In adults with darker skin, the melanomas were more common in lower limbs, hips, and trunk, but in adults with lighter skin, melanomas were more predominant in sun-exposed sites, especially the head and neck, but could also be found in the trunk and upper limbs. [41][42][43][44] Possible differences in sun exposure behaviors might result in different sites of melanoma occurrence. 5 In our study, we have found that the majority of our melanomas have developed in the trunk with the highest mortality at 38%.…”
Section: Anatomical Distributionmentioning
confidence: 99%